Life Cycle Greenhouse Emissions of Compressed Natural Gas-Hydrogen Mixtures for Transportation in Argentina - Martinez, Pablo Enrique (2010)
We have developed a model to assess the life cycle greenhouse emissions of compressed natural gas-hydrogen (CNG-H2) mixtures used for transportation in Argentina. The overall fuel life cycle is assessed through a well-to-wheel (WTW) analysis for different hydrogen generation and distribution options. The combustion stage in road vehicles is modeled using the COPERT IV model. Hydrogen generation options include classical steam methane reforming (SMR) and water electrolysis (WE) in central plants and distributed facilities at the refueling stations. Centralized hydrogen generation by electrolysis in nuclear plants as well as the use of solar photovoltaic and wind electricity is also considered. Hydrogen distribution options include gas pipeline and refrigerated truck transportation for liquefied hydrogen. A total number of fifteen fuel pathways are studied; in all the cases the natural gas-hydrogen mixture is made at the refueling station. The use of WE using nuclear or wind electricity appears to be less contaminant that the use of pure CNG.